Perancangan Sistem Informasi Quality Control Berbasis Web Pada PT. Pelangi Indah Canindo. Tbk - Sandi Ocviana; Sofa Sofiana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT. Pelangi Indah Canindo, Tbk is a company that produces Steel Drum (packaging for oil, oil, paint, and other liquid materials). This company is already computerized based, but the work process is still not optimal because the recording of test results and the making of test reports carried out by quality control staff is still done manually by recording the test results on checksit paper then transferred to a ledger and submitting the test results the quality control manager so that the recording of the test results takes a long time and errors can occur in recording the test results. To solve this problem, a web-based quality control information system was designed which was created using the PHP programming language and using Mysql as a DBMS (Database Management System). To find out the internal and external strengths of the company, researchers use the Unified Modeling language (UML) to analyze the system design that will be made. The test method that will be carried out is black box testing. With the system that will be created, it can help staff quality control and simplify and speed up the process of submitting the data to the quality control manager.a